Teachers’ Perceptions of Arabic Language Learning Evaluation: A Descriptive Qualitative Studypaper - Irpan Ismail Muhammad Noor (Pusaka Cendekia Indonesia Foundation, 2025)
The present study aims to provide an in-depth description of teachers’ perceptions of evaluation in Arabic language learning, including its purposes, functions, techniques, instruments, and the factors influencing its implementation in schools. In addition, this research seeks to understand how teachers perceive the effectiveness of evaluation in improving students’ learning outcomes. This study employed a descriptive qualitative method using a literature-based approach combined with primary data collected through in-depth interviews with Arabic language teachers. Secondary data were obtained from evaluation documents, instructional materials, and relevant literature. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, complemented by triangulation to ensure data validity. The findings reveal that teachers perceive evaluation as an essential component for measuring students’ abilities and the attainment of Arabic language learning objectives. However, its implementation still faces several challenges, including limited time allocation, insufficiently varied instruments, and the low utilization of formative assessment. Teaching experience, pedagogical understanding, and institutional support were found to influence teachers’ perceptions and practices in conducting evaluation. Furthermore, teachers believe that evaluation has the potential to enhance students’ learning outcomes; however, its effectiveness depends on the quality of the instruments, consistency of implementation, and appropriate follow-up measures such as feedback, remedial activities, and enrichment. Therefore, enhancing teachers’ competence in designing authentic assessments is necessary to optimize learning outcomes. Penelitian ini bertujuan untuk mendeskripsikan secara mendalam persepsi guru terhadap evaluasi pembelajaran Bahasa Arab, meliputi tujuan, fungsi, teknik, instrumen, serta faktor-faktor yang memengaruhi implementasinya di sekolah. Selain itu, penelitian ini bertujuan memahami bagaimana guru menilai efektivitas evaluasi dalam meningkatkan capaian belajar siswa. Metode yang digunakan adalah penelitian deskriptif kualitatif dengan pendekatan studi pustaka dan pengumpulan data primer melalui wawancara mendalam kepada guru Bahasa Arab. Data sekunder diperoleh dari dokumen evaluasi, perangkat pembelajaran, serta literatur relevan. Analisis data dilakukan menggunakan model Miles dan Huberman melalui proses reduksi, penyajian, dan penarikan kesimpulan, dilengkapi triangulasi untuk menjamin keabsahan data. Hasil penelitian ini menunjukkan bahwa guru memandang evaluasi sebagai bagian penting dalam mengukur kemampuan siswa dan pencapaian tujuan pembelajaran Bahasa Arab. Namun, pelaksanaannya masih menghadapi kendala seperti keterbatasan waktu, instrumen yang kurang bervariasi, serta rendahnya pemanfaatan evaluasi formatif. Faktor pengalaman mengajar, pemahaman pedagogik, dan dukungan sekolah memengaruhi persepsi guru dalam melaksanakan evaluasi. Selain itu, guru menilai bahwa evaluasi memiliki potensi meningkatkan capaian belajar siswa, tetapi efektivitasnya bergantung pada kualitas instrumen, konsistensi pelaksanaan, dan tindak lanjut berupa umpan balik, remedial, serta pengayaan. Dengan demikian, peningkatan kompetensi guru dalam merancang evaluasi autentik diperlukan untuk mengoptimalkan hasil pembelajaran.